A comprehensive outline of antimicrobial resistance, antibiotic prescribing, and antimicrobial stewardship in South Africa: A scoping review protocol - Suwayda Ahmed; Rukshana Ahmed; Razia Zulfikar Adam (PLoS ONE, 2025)
Introduction The global prevalence of antimicrobial resistance transcends geographical and economic boundaries, affecting populations worldwide. Excessive and incorrect use of antibiotics encourages antimicrobial resistance which leads to complex treatment strategies for infectious diseases and possible failure of treatment. The incorrect and unnecessary prescribing of antibiotics places a burden on healthcare costs and thus, antimicrobial resistance is evident globally as a major public health concern. The impact is particularly pronounced in low to middle-income countries, where limited access to healthcare exacerbates the crisis. This scoping review aims to comprehensively map the evidence of antimicrobial resistance in healthcare settings, encompassing the exploration of antibiotic prescribing practices and the implementation of antimicrobial stewardship initiatives in South Africa. Methodology This protocol has been registered in the Open Science Framework (https://doi.org/10.17605/OSF.IO/PWMFB). This review will consider all types of study designs, conducted within South Africa. Studies that are published in English for the period 2019–2024, and that explore antimicrobial resistance (AMR) evidence in healthcare in South Africa, including antibiotic prescribing trends and antimicrobial stewardship and surveillance initiatives will be included. Non-English publications, studies outside of South Africa, animal and environmental studies will be excluded. The criteria for the scoping review will be set by two reviewers. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) tool will be used. Studies will be identified through an extensive search of peer-reviewed and grey literature databases. The results of the review will be tabulated and include a narrative synthesis of the findings.